2011
DOI: 10.1590/s0037-86822011005000040
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological study of human cysticercosis with blood samples collected on filter paper, in Lages, State of Santa Catarina, Brazil, 2004-2005

Abstract: INTRODUCTION: Human serofrequency of antibodies against Taenia solium antigens was determined and risk factors for cysticercosis transmission were identified. METHODS: Individuals (n=878) from periurban and rural locations of Lages, SC, were interviewed to gather demographic, sanitary and health information. Interviews and blood sample collections by finger prick on Whatman filter paper were performed from August 2004 to May 2005. Observation determined that 850 samples were suitable for analysis and were test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…En Latinoamérica, se han hecho varios estudios epidemiológicos que demuestran la relevancia de la enfermedad, principalmente en Perú (11-13), México (14-16), Brasil (17)(18)(19), Ecuador (20) y Colombia (21). En un trabajo de 2014 en Colombia, se describió la cisticercosis como una enfermedad desatendida y reemergente (22), al igual que en un gran estudio del 2013, en el cual se analizaron 23.960 muestras provenientes de 23 departamentos colombianos, incluida la capital, y se obtuvo una seroprevalencia general de 8,55 %, con un rango entre 0,53 y 40,19 % (23).…”
unclassified
“…En Latinoamérica, se han hecho varios estudios epidemiológicos que demuestran la relevancia de la enfermedad, principalmente en Perú (11-13), México (14-16), Brasil (17)(18)(19), Ecuador (20) y Colombia (21). En un trabajo de 2014 en Colombia, se describió la cisticercosis como una enfermedad desatendida y reemergente (22), al igual que en un gran estudio del 2013, en el cual se analizaron 23.960 muestras provenientes de 23 departamentos colombianos, incluida la capital, y se obtuvo una seroprevalencia general de 8,55 %, con un rango entre 0,53 y 40,19 % (23).…”
unclassified
“…In Latin America, several epidemiological studies demonstrated the relevance of the disease in Mexico (Fleury et al 2010), Peru , and Brazil (Ishida et al 2011). Other authors confirmed the significance of taeniosis/cysticercosis in Guatemala (García-Noval et al 1996), Honduras (Sánchez et al 1999), Bolivia (Carrique-Mas et al 2001), Ecuador (Rodríguez-Hidalgo et al 2006, Colombia (Sanzón et al 2002), and Venezuela (Ferrer et al 2003a;Cortez et al 2010); more recently, a systematic review and meta-analysis of the literature found a consistent association between epilepsy and NCC in Latin American countries (Bruno et al 2013).…”
Section: The Agentmentioning
confidence: 99%
“…In another study, a prevalence of 5.7% was reported for IgG antibody detection in a rural settlement in São Paulo ( 9 ). In the southern region, CC seroprevalence was 3.4% in Lages-SC ( 10 ). In the Midwest, a study demonstrated a seroprevalence of 13.8% for CC in adults living in the municipality of Jataí-GO ( 11 ).…”
Section: Introductionmentioning
confidence: 99%